Likuiditas, leverage, arus kas dan ukuran perusahaan sebagai determinan faktor financial distress - Mulya, Anissa Amalia; Andini, Prita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
One of the ways used to predict the existence of financial distress conditions is to measure financial performance indicators from the company's financial statements published by the company. In this study, the financial performance used to predict financial distress is liquidity, leverage, cash flow and company size. This research is a causal associative research using a quantitative approach, the population used is 32 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. Sampling using purposive sampling method. The type of data used is secondary data. Data analysis using multiple linear regression models using the Statistical Product and Service Solutions (SPSS V.26) calculation program. Liquidity and Cash Flow have a negative and significant effect on financial distress, Leverage has a positive and significant effect on financial distress and Company size has no effect on financial distress. So it is concluded that the size of the company cannot determine financial distress in a company.